2000
DOI: 10.1093/jn/130.10.2568
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Lipogenic Enzyme Activity, trans Fatty Acids and Conjugated Linoleic Acids Are Altered in Lactating Dairy Cows Fed a Milk Fat–Depressing Diet

Abstract: The objectives of the present study were to examine the effect of a milk fat-depressing (MFD) diet on: 1) the activity of mammary acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS), 2) ACC mRNA relative abundance and 3) distributions of conjugated linoleic acids (CLA) and trans-18:1 fatty acids (tFA) in milk fat. Twelve lactating Holstein cows were used in a single reversal design. Two diets were fed: a control diet (60:40% forage/concentrate) and an MFD diet (25:70% forage/concentrate, supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
224
12
31

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(295 citation statements)
references
References 39 publications
28
224
12
31
Order By: Relevance
“…Mammary lipogenic capacity may be regulated at multiple levels including transcription, translation, protein turnover and enzyme activity. Decreased mammary expression of genes for key enzymes and proteins involved in FA uptake, synthesis, transport and esterification occurred during both diet-and CLA-induced MFD (Piperova et al, 2000;Ahnadi et al, 2002;Baumgard et al, 2002b;Peterson et al, 2003;. Combined, these observations define MFD as a decreased mammary capacity for lipid synthesis due to a coordinated transcriptional down-regulation of enzymes and proteins involved in milk fat synthesis.…”
Section: Mechanism Of Milk Fat Depressionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mammary lipogenic capacity may be regulated at multiple levels including transcription, translation, protein turnover and enzyme activity. Decreased mammary expression of genes for key enzymes and proteins involved in FA uptake, synthesis, transport and esterification occurred during both diet-and CLA-induced MFD (Piperova et al, 2000;Ahnadi et al, 2002;Baumgard et al, 2002b;Peterson et al, 2003;. Combined, these observations define MFD as a decreased mammary capacity for lipid synthesis due to a coordinated transcriptional down-regulation of enzymes and proteins involved in milk fat synthesis.…”
Section: Mechanism Of Milk Fat Depressionmentioning
confidence: 87%
“…Piperova et al (2000) reported decreased mammary enzyme activity of acetyl-CoA carboxylase (ACC) and fatty acid synthase (FASN) during diet-induced MFD and Baumgard et al (2002b) observed decreased mammary lipogenic capacity during CLA-induced MFD based on 14 C acetate incorporation into FA by mammary tissue explants. This demonstrates an inhibition of milk fat synthesis in the mammary gland and is in agreement with the decrease in de novo-synthesized FA previously discussed.…”
Section: Mechanism Of Milk Fat Depressionmentioning
confidence: 99%
“…A number of studies have demonstrated that increasing amounts of readily digestible carbohydrates in the diet are associated with increased proportions of trans10,cis12-CLA and trans10-C18:1 in milk fat [4][5][6]16]. The fact that the concentrate level only affected trans10,cis12-CLA and trans10-C18:1 but also the cis9,trans11-CLA and trans11-C18:1 concentration in milk when maize silage was fed, suggests that increased proportions of concentrate (starch) in the diet does not severely affect the ruminal biohydrogenation pattern unless combined with a forage naturally high in starch.…”
Section: Discussionmentioning
confidence: 99%
“…However, diets that provide large amounts of readily digestible carbohydrates such as starch, with [4,5] or without [6,7] a supplement of vegetable oil often lead to increased proportions of trans10-C18:1 and trans10,cis12-CLA in milk fat. This response is usually caused by a decline in rumen pH [4,6] and shifts in the bacterial populations [8] whereby the biohydrogenation pathway of C18:2n−6 is altered [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation